Bio-behavioral survey of syphilis in homeless men in Central Brazil: a cross-sectional study - Cleiciane Vieira de Lima Barros; Hélio Galdino Júnior; Giovanni Rezza; Rafael Alves Guimarães; Priscilla Martins Ferreira; Christiane Moreira Souza; Lara Cristina da Cunha Guimarães; David Antônio Costa Barros; Sandra Maria Brunini (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2018)
The objective of this study was to investigate the prevalence and factors associated with syphilis in homeless men in Central Brazil. It is a cross-sectional study conducted with 481 individuals attending four therapeutic communities between October and December 2015. A structured interview was conducted to collect sociodemographic data and risk factors for syphilis. Rapid/point-of-care and VDRL tests were performed to determine exposure to syphilis and the presence of active syphilis, respectively. Poisson regression analysis was used to verify the risk factors associated with the outcomes investigated. Of the study participants, 10.2% were reactive to the rapid test, and 5.4% had active syphilis. At the multiple regression analysis, schooling (adjusted prevalence ratio - APR: 0.89; p = 0.005), history of genital ulcer (APR: 2.59; p = 0.002), STI history (APR: 1.97; p = 0.042), and sexual intercourse under drug effects (APR: 1.60; p = 0.022) were independent factors associated with lifetime syphilis. Also, history of genital ulcer (APR: 2.19; p = 0.019), STI history (APR: 1.74; p = 0.033) and number of sexual partners in the last year (APR: 1.02; p = 0.044) were associated with active syphilis. The prevalence of syphilis among homeless men was rather high, confirming the vulnerability of this group to this infection. These results emphasize the need for educational intervention, improvement of risk reduction programs, availability of diagnostic tests, especially the rapid test, and treatment.